KUALITAS SUMBER DAYA DALAM IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERKOTAAN (PNPM-MP) DI KELURAHAN KOTA BARU KOTA PONTIANAK - Lusmana E.01110103, Rahmah Inda (FISIP Universitas Tanjungpura, 2014)
The purpose of this study is intended to provide an understanding of the quality of resources in the implementation of the national program of urban self- empowerment ( PNPM - MP ) in the Village of New Town Pontianak .The method used is descriptive research that the author wanted to illustrate how the quality of resources in the implementation of PNPM - MP in the Village of New Town Pontianak .Existing problems in the implementation of PNPM - MP is quite interesting to study considering there are still some things that cause less successful implementation of PNPM - MP if viewed from resource factors . Factors - the factors that lead to less successful in implementing resource PNPM - MP is the staff , information , authority and facilities . In addition there are other factors such as the difficulty in recruiting or retaining qualified resources and establishment of harmony between the implementor in the implementation of PNPM - MP in the Village of New Town Pontianak .Suggestions can be taken into consideration , namely the staff or HR ( human resources ) in the implementation of PNPM - MP given more training to build to improve motivation, human resources in the implementation of PNPM - MP still need a companion of facilitators, the government should provide more timely funds will be given to activities in each Village BKM , every KSM should only focus on the future course of the business can be a hallmark of the New City Village , the government should also pay attention to add the costs of implementing programs PNPM - MP , and every implementor PNPM - MP should be able to establish a good relationship .Keywords : Resources , Implementation , PNPM - MP , New City Village , Staff , Information , Authority , Facilities